Nondimensional sediment transport capacity of sand soils and its response to parameter in the Loess Plateau of China. Issue 3 (15th November 2019) - Li, Pu; Zhang, Kuandi; Wang, Jingwen; Meng, He
Abstract: Soil erosion is a major contributor to land degradation in the Loess Plateau in China. To clarify the sediment transport capacity of overland flow influenced by hydraulic parameters, such as shear stress, sand shear stress (hydraulic gradient partition method and hydraulic radius partition method), mean flow velocity, Froude number, stream power, and unit stream power, indoor experiments with eight‐unit‐width flow discharges from 0.0667 × 10 −3 to 0.3333 × 10 −3 m 2 ·s −1, six slope gradients from 3.49 to 20.79%, and two kinds of sand soils ( d 50 = 0.17 and 0.53 mm) were systematically investigated. A nondimensional method was adopted in data processing. Results showed that there was a partition phenomenon of relation curves because of the different median grain diameters. The correlation between the nondimensional stream power and nondimensional sediment transport capacity was the highest, followed by the correlation between the nondimensional unit stream power and nondimensional sediment transport capacity. However, there was a poor correlation between the flow intensity indices of velocity category and nondimensional sediment transport capacity. Nondimensional stream power, nondimensional unit stream power, and nondimensional shear stress could predict sediment transport capacity well. Ignoring the partition phenomenon of the relation curves, stream power could be used to predict sediment transport capacity, with a coefficient of determination of .85. Furthermore, a general flow intensity index was obtained to predict sediment transport capacity of overland flow. Finally, an empirical formula for predicting sediment transport capacity with a coefficient of determination of .90 was established by multiple regression analyses based on the general flow intensity index. During the analysis between measured sediment transport capacities in present study and predicted values based on Zhang model, Mahmoodabadi model, and Wu model, it was found that these three models could not accurately predict sediment transport capacities of this study because different models are estimated on the basis of different experimental conditions. Abstract : 1 There was a poor correlation between the flow intensity indices of velocity category and nondimensional sediment transport capacity.2 Ignoring the partition phenomenon of the relation curves, stream power can be used to predict sediment transport capacity, with a coefficient of determination of 0.85.3 An empirical formula for predicting sediment transport with a coefficient of determination of 0.90 was established by multiple regression analysis based on the general flow intensity index.